2023
DOI: 10.15835/nbha51113029
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment effect on tocopherols, total phenolics and fatty acids in table olives (Olea europaea L.)

Abstract: The olive fruits are rich source of oil, vitamins, minerals, organic acids and pigments. The fruits contain high level of bioactive compounds. The aim of this study was to examine the effect of heat treatment on tocopherols, total phenolics and antioxidant activity in green and black olives, as well as their fatty acid composition. The instrumental methods used in this experiment were high performance liquid chromatography (HPLC), gas chromatography with flame ionization detection (GC/FID) and spectrophotometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…In addition, Kmiecik et al (2023) demonstrated that heating olive oil resulted in degradation, affecting lipid nutritional indices and tocopherol content. In addition, Mihajlovic et al (2023) observed reductions in tocopherols and TP in olives after heat treatment, with significant changes in fatty acid composition, particularly in polyunsaturated fatty acids Adding different concentrations (250-1,000 ppm) of C. vulgaris ultrasonic extract as well as 200 ppm of BHT into heated AO can indeed reduce the changes that occur in fatty acids. Increasing the concentration of C. vulgaris ultrasonic extract in heated AO may indeed decrease the changes in fatty acids affected by heat treatment.…”
Section: Oxidative Stability Of Avocado Oilmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, Kmiecik et al (2023) demonstrated that heating olive oil resulted in degradation, affecting lipid nutritional indices and tocopherol content. In addition, Mihajlovic et al (2023) observed reductions in tocopherols and TP in olives after heat treatment, with significant changes in fatty acid composition, particularly in polyunsaturated fatty acids Adding different concentrations (250-1,000 ppm) of C. vulgaris ultrasonic extract as well as 200 ppm of BHT into heated AO can indeed reduce the changes that occur in fatty acids. Increasing the concentration of C. vulgaris ultrasonic extract in heated AO may indeed decrease the changes in fatty acids affected by heat treatment.…”
Section: Oxidative Stability Of Avocado Oilmentioning
confidence: 88%
“…In addition, Kmiecik et al (2023) demonstrated that heating olive oil resulted in degradation, affecting lipid nutritional indices and tocopherol content. In addition, Mihajlovic et al (2023) observed reductions in tocopherols and TP in olives after heat treatment, with significant changes in fatty acid composition, particularly in polyunsaturated fatty acids…”
Section: Hplc Analysismentioning
confidence: 92%